O processo de indicação geográfica na Região Oeste do Paraná: um estudo de caso na Cooperativa de Mel - Coofamel - Sígolo, Érick Antonio (2019)
Geographical Indication (GI) is related to the perception of the own companies and the consumer in regards to changes in production, considering factors such as product origin, culture, customs and the valorization of the physical aspects related to the place of origin and the quality of the product. The fact is that there are contractual characteristics of transaction cost, which influence the understanding and the governance mechanisms of the organizations. In this sense, the objective of this research was to analyze the influence of the institutional environment and the organizations that helped to establish the GI for honey in the Western Region of Paraná. The case study owned, as methodology, the descriptive research that seeks to elucidate characteristics of its nature, causes, relations, among other factors of a certain population, in order to establish the variables to be analyzed. Primary data were obtained through a specific form among the members and the president of a specific cooperative; secondary data were obtained through reports and observation at the research site. Data analysis was performed with the use of Excel Software, employing descriptive statistics with quantitative and qualitative approach. It was possible to identify MAPA, Anvisa, Sebrae, Biolabore, Unioeste and Prefectures as the main institutions and organizations in the process of implementation and management of the GI of honey in the Western Region of Paraná. In the social aspect, it was verified a limited rationality and opportunisms of the economic agents and the attributes of frequency and uncertainty inherent to the transaction cost. Finally, it was identified that the cooperative needs to improve its process of coordination and communication with the associate in a way that qualifies its governance structure.